Contaminante emergente: investigação da atenuação no crescimento da macrófita aquática (Ricciocarpus natans) exposta ao surfactante - Araújo, Jesuino Souza (Universidade Federal de São Carlos, 2022)
Motivated by the environmental impacts that emerging contaminants can cause in ecosystems, especially in water bodies, this study investigated the change in the growth of Ricciocarpus natans when exposed to the surfactant sodium dodecyl sulfate (SDS). For this purpose, bioassays were carried out with 40 individuals of equivalent initial sizes, divided into four groups of 10 individuals (20 maintained in the control condition and 20 in a medium containing surfactant). After collected, the specimens of R. natans were washed and distributed in four beakers filled with water (≈ 200 ml) collected in the Monjolinho reservoir. Two beakers were designed for the control group and two with the addition of 1,4 mg L-¹ of DSS; then they were placed in a germination chamber at 25 oC and photoperiod of 12 h light/12 h dark. The experiment consisted of measuring the length of individuals for 10 weeks. With the temporal variation of the length of the specimens of R. natans, it was adjusted to the exponential model. Comparing the doubling times, it was observed that the control group was 45.5 days (0.0153 day-1) and for the treatment with DSS it was 73.7 days (0.0094 day-1) i.e., the growths were 1.6 times greater in the control treatment. When comparing the temporal variation of the length of R. natans, there was a significant difference between the two treatments (p < 0.05). Following the premise that the surfactant has an inhibitory action on the growth of macrophytes, bringing a negative influence of the contaminant on the growth coefficient of R. natans; the analysis of the results also showed that there was a reduction in growth from the first week of the experiment. The indiscriminate use and disposal of compounds with surfactants sends an alert to society in general, governments and legislators, as well as to academia and companies in tackling the problem, with relevant legislation, funding, research, and social awareness.
Emerging contaminant: investigation of attenuation in the growth of aquatic macrophyte (Ricciocarpus natans) exposed to surfactant
Keywords: Modelo matemático; Corpos hídricos; Contaminante; Dodecil sulfato de sódio; Crescimento; Mathematical model; Water bodies; Contaminant; Sodium dodecyl sulfate; Growth; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS